1996
DOI: 10.1017/s0266466600006642
|View full text |Cite
|
Sign up to set email alerts
|

The Estimation of Continuous Parameter Long-Memory Time Series Models

Abstract: A class of univariate fractional ARIMA models with a continuous time parameter is developed for the purpose of modeling long-memory time series. The spectral density of discretely observed data is derived for both point observations (stock variables) and integral observations (flow variables). A frequency domain maximum likelihood method is proposed for estimating the longmemory parameter and is shown to be consistent and asymptotically normally distributed, and some issues associated with the computation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 15 publications
0
54
0
Order By: Relevance
“…with some constants C > 0, γ > 0 and β > 1/4, then 10) and hence the asymptotic relations (3.4) and (3.5) …”
Section: The Approach and Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…with some constants C > 0, γ > 0 and β > 1/4, then 10) and hence the asymptotic relations (3.4) and (3.5) …”
Section: The Approach and Resultsmentioning
confidence: 96%
“…An example of a continuous-time model that displays the above defined memory structures is the continuous-time autoregressive fractionally integrated moving-average (CARFIMA) process (see, e.g., Chambers [10], Tsai and Chan [29]). …”
Section: Introductionmentioning
confidence: 99%
“…For the special case of fractional integration, spectral results have been obtained by Chambers (1998), Hwang (2000, Chan (2005b), andSouza (2005). Further, Chambers (1996) and Tsai and Chan (2005a) cover the related case of discrete-time sampling from a continuous-time long memory process, while Souza (2007Souza ( , 2008 focusses on the effect of temporal aggregation on widely used memory estimators.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that data in many fields of application (including geostatistics, hydrology, turbulence, economics, and finance) display fractal structure (see Adler (1981), Hosking (1981), Chambers (1996), Woyczyński (1998), Hilfer (2000), Christakos (2000), and the references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, Granger and Joyeux (1980) and Hosking (1981) constructed long-memory time series in discrete time via fractional differencing, and Chambers (1996) used fractional derivatives to obtain long-memory phenomena for continuous-time stochastic processes. Some other examples of fractional random fields can be found in Anh et al (1999), Anh and Leonenko (2000), (2001), (2002) and Ruiz-Medina et al (2001), (2003), (2004).…”
Section: Introductionmentioning
confidence: 99%